Protection of Human Rights by Law Enforcement Officers Against the Actions of Armed Criminal Groups (KKB) in Papua - I Nyoman Sucitrawan; Bayu Dwi Anggono; Fanny Tanuwijaya (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2024)
A terrorist group called the Papuan Armed Criminal Group (KKB) located in Papua Province. KKB was formerly known as the Free Papua Organization (OPM) which was founded in 1965 with the aim of breaking away from Indonesia (committing separatist acts) and making various efforts to conduct a referendum in order to become independent from the Unitary State of the Republic of Indonesia. This Normative Legal Research Method is an internal research in the discipline of law that uses sources of legal material in the form of laws and regulations, court decisions / decrees, contract agreements, contracts, legal theories and opinions of scholars. The 1945 Constitution and humanitarian law also accommodate the protection of civilians in conflict areas. This basic principle upholds the basic principle of respect for individuals, as well as the protection of human rights victims. The Special Autonomy Law is considered a strategic policy in order to improve services, accelerate, develop, and empower all people in the Papua region. One of the obligations that must be fulfilled by the State is the protection of every citizen. Indonesia as a country that upholds human rights should protect all its citizens, not only fulfilling obligations, the state has also fulfilled the human rights of its citizens. The government has adopted several policies, one of which is Law Number 21 of 2001 concerning Special Autonomy for Papua, also known as Otsus Papua.